Pengendalian Alih Fungsi Lahan Pertanian di Kawasan Perkotaan Mangupura Kabupaten Badung - Widiarsa, I Putu Anom; Suartika, Gusti Ayu Made (RUANG: Jurnal Lingkungan Binaan (SPACE: Journal of the Built Environment); Vol 5 No 2 (2018): October 2018, 2018)
This article aims at analyzing determining aspects that must be incorporated in to the process of developing a strategy to control land development. It converses this objective by taking the increasing rate of agricultural land conversion in Mangupura urban area, of Badung Regency-Bali, as its case study. The study was carried out using a qualitative approach. The findings demonstrate the driving factors behind such a conversion are classified into four categories, including social, economical, environmental and regulatory forces. Learning from the dynamic of land development of Mangupura area, the study subsequently comes out with a conclusion that for efficiency and success, the strategy to control land use changes has to embrace two basic aspects of: (i) identification and clarification of instruments to regulate spatial changes, and (ii) the allocation of agency/s assigned to carry out the controlling roles. It is further emphasized that attempts to rule spatial development should take both of the aforementioned determining forces and basic aspects influencing the success of the control strategy, into account. Keywords: conversion, agricultural land, land use control and strategy